Colonial landscapes: Cities and Infrastructures in former Portuguese Southern African colonies - A brief historiographical analysis based on the colonial transport networks - Milheiro, A. V. (African Geographical Review, 2021)
This article is part of the research project ‘Coast to Coast– Late Portuguese Infrastructural Development in Continental Africa (Angola and Mozambique): Critical and Historical Analysis and Postcolonial Assessment’ funded by Foundation for Science and Technology. Its aims to contribute to expanding the historiographical debate on the repercussions of the decisions taken by the Portuguese through the perspective of transport and territorial mobility during the colonial period, considering the late Constitutional Monarchy; the First Republic; and the Estado Novo dictatorship. The main sources used are related to the Colonial Public Works reports released from the late 19th century onwards.